2001
DOI: 10.1038/sj.gt.3301431
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type p53 gene transfer inhibits neointima formation in human saphenous vein by modulation of smooth muscle cell migration and induction of apoptosis

Abstract: Patency of autologous human saphenous vein coronary artery bypass grafts (CABG) is compromised by intimal thickening and superimposed atherosclerosis, caused by migration of vascular smooth muscle cells (SMC) to the intima where they proliferate. Here, using adenoviral transfer, we have targeted SMCs using wild-type p53 (wt p53) overexpression. Initial in vitro analyses demonstrated that wt p53 overexpression had no effect on SMC proliferation but promoted apoptosis, which was inhibited by co-expression of bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 31 publications
7
63
0
Order By: Relevance
“…28,35,36 In agreement with this, we found that serum deprivation of wild-type or mock-transfected VSMC-E1A cells resulted in rapid induction of p53 (Ϸ4-fold increase 1 hour after deprivation; Figure 6A). In contrast, the induction of p53 in mortalin-transfected cells was delayed for about 6 hours ( Figure 6A), suggesting that mortalin may inhibit apoptosis in VSMCs by reducing the level of p53.…”
Section: Mortalin Inhibits Apoptosis In Vsmcs Via the Inactivation Ofsupporting
confidence: 71%
“…28,35,36 In agreement with this, we found that serum deprivation of wild-type or mock-transfected VSMC-E1A cells resulted in rapid induction of p53 (Ϸ4-fold increase 1 hour after deprivation; Figure 6A). In contrast, the induction of p53 in mortalin-transfected cells was delayed for about 6 hours ( Figure 6A), suggesting that mortalin may inhibit apoptosis in VSMCs by reducing the level of p53.…”
Section: Mortalin Inhibits Apoptosis In Vsmcs Via the Inactivation Ofsupporting
confidence: 71%
“…In particular, an important role of p53 in the pathogenesis of vascular diseases is suggested by decreased p53 levels in human restenotic (22) and atherosclerotic lesions (23). The importance of p53 is also confirmed in various animal models.…”
Section: Apoptosis Of Vascular Smooth Muscle Cells (Smcs)mentioning
confidence: 60%
“…In addition, several lines of evidence have suggested the functional linkage between TP53 and cell invasion and motility. For example, the overexpression of TP53 significantly reduced the invasion and migration of vascular smooth muscle cells (SMC) [5]. The deletion of TP53 led to actin cytoskeleton reorganization and a significant increase in cell motility in mouse embryonic fibroblast cells [6].…”
Section: Introductionmentioning
confidence: 99%